2023
DOI: 10.1161/circheartfailure.122.010351
|View full text |Cite
|
Sign up to set email alerts
|

Nonsense Variant PRDM16-Q187X Causes Impaired Myocardial Development and TGF-β Signaling Resulting in Noncompaction Cardiomyopathy in Humans and Mice

Bo Sun,
Omid M.T. Rouzbehani,
Ryan J. Kramer
et al.

Abstract: BACKGROUND: PRDM16 plays a role in myocardial development through TGF-β (transforming growth factor-beta) signaling. Recent evidence suggests that loss of PRDM16 expression is associated with cardiomyopathy development in mice, although its role in human cardiomyopathy development is unclear. This study aims to determine the impact of PRDM16 loss-of-function variants on cardiomyopathy in humans. METHODS: Individuals with PRD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 57 publications
1
0
0
Order By: Relevance
“…Consistent with its known role as a negative regulator of TGFβ signaling, 39,42,43 KEGG pathway analysis indicated that Prdm16 controlled TGFβ signaling in BOECs. Additionally, Prdm16 also modulated NOTCH signaling ( Fig.S4A; TableS5 ), which is essential for arterial lineage specification and arterial development, as perturbations in Notch signaling cause aberrant arterial development and AVMs.…”
Section: Resultssupporting
confidence: 53%
“…Consistent with its known role as a negative regulator of TGFβ signaling, 39,42,43 KEGG pathway analysis indicated that Prdm16 controlled TGFβ signaling in BOECs. Additionally, Prdm16 also modulated NOTCH signaling ( Fig.S4A; TableS5 ), which is essential for arterial lineage specification and arterial development, as perturbations in Notch signaling cause aberrant arterial development and AVMs.…”
Section: Resultssupporting
confidence: 53%